TEACHER DIFFICULTIES AND STRATEGIES IN MANAGING A LARGE CLASS IN TEACHING AND LEARNING ENGLISH - Wahyu Indah Pertiwi; Niken Reti Indriastuti (EDUPEDIA, 2020)
This research aims to describe the difficulties faced by teachers in managing a large class and the teacher strategies in managing a large class. This research is a qualitative descriptive research with the subject one of the English teachers of SMA N 1 Badegan and students of Class XI MIPA 1- XI MIPA 4 as participants. Data collection techniques in this study were interviews and questionnaire. The results showed that in teaching and learning English in a large class, there were found three main challenges that must be faced by the teacher, namely the difficulty in giving attention to each individual in the class, heterogeneous student abilities and the difference of student background knowledge. The strategies used by the teacher to solve the problems in managing large classes include division of heterogeneous groups, small-group strategies, peer tutoring, visual imagery, and translation strategies. The application of classroom management skills includes asking skills, explaining skills, variation skills, and teaching a group and individual skills.